Foreign investment, human rights and the environment : a perspective from South Asia on the role of public international law for development - Puvimanasinghe, Shyami Fernando (Martinus Nijhoff, 2007)
Embodies a critique of the complex web of public international law principles on economics, human rights and the environment, and their convergence or lack thereof, related regional (South Asian) and domestic (Sri Lankan) legal arrangements, interventions of states and non-state actors towards just, equitable and sustainable development.